Ceramic firing carrier

By using boron nitride sintered plates with high porosity and appropriate pore diameter distribution as a carrier for ceramic firing, the problems of undersized sintering and uneven color are solved, and the high airtightness and strength of the ceramic plate are improved. .

CN116981650BActive Publication Date: 2025-01-17DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280020572.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-28
Publication Date
2025-01-17
Estimated Expiration
2042-03-28

AI Technical Summary

Technical Problem

The existing ceramic plate formed by hexagonal boron nitride powder has problems such as insufficient sintering and uneven color during the firing process, and the insufficient shrinkage of the pore diameter of the carrier causes the sintering additive to escape, affecting the strength of the ceramic plate and quality.

Method used

The boron nitride sintered plate with a plurality of pores is used as a ceramic sintering vehicle, the porosity is 8 volume % or more, and the pore diameter is 0.2 to 0.9 μm is 76 to 95%, and the boron nitride is passed at high temperature. The thermal expansion and contraction of the sintered plates to improve the shrinkage rate of the pore diameter, inhibit the escape of the sintering additives, and enhance the airtightness.

Benefits of technology

It is achieved that the airtightness and strength of the ceramic plate are improved while not hindering the escape of gas during the ceramic firing process, reducing color unevenness, and ensuring high-quality molding of the ceramic plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116981650B_ABST
    Figure CN116981650B_ABST
Patent Text Reader

Abstract

One aspect of the present invention provides a ceramic sintering carrier, which is composed of a boron nitride sintered plate having a plurality of pores, wherein the porosity is 8% by volume or more, and the proportion of pores with a pore diameter of 0.2 to 0.9 μm measured by a mercury porosimeter is 76 to 95% of all pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carrier for sintering ceramics. Background Art

[0002] Hexagonal boron nitride has lubricity, heat resistance, high thermal conductivity, mold release, reactivity resistance, and insulation. In addition to its uses as a solid lubricant, thermal conductive filler, and insulating filler, it can also be used as a setter when firing ceramic raw materials.

[0003] The carrier is a plate used as a mounting table or a weight material when firing a green sheet containing a ceramic raw material and a binder resin or manufacturing a ceramic plate. The carrier is generally a porous sintered body, and at least a part of the gas generated when the green sheet is degreased can escape to the outside through the pores of the porous body.

[0004] The properties of ceramic plates manufactured using a carrier are affected by the carrier. For example, if the carrier is curved, its shape is transferred to the green sheet, resulting in a deformed ceramic plate. In addition, the ceramic plate from the green sheet that is in direct contact with the carrier may adhere to the carrier, so defects such as cracks may occur when peeling. Therefore, research has been conducted to alleviate the above-mentioned issues for carriers formed using hexagonal boron nitride powder.

[0005] For example, Patent Document 1 describes a ceramic firing carrier characterized by being formed of a boron nitride sintered body having an average pore diameter of 0.1 to 0.4 μm and a bending strength of 15 MPa or more.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 09-278526 Summary of the invention

[0009] Problems to be solved by the invention

[0010] According to the research of the inventors of the present application, even when a carrier formed of hexagonal boron nitride powder is used, the quality of the obtained ceramic plate varies. For example, it may happen that the strength of the ceramic plate cannot be exerted due to insufficient sintering, and sometimes color unevenness is observed on the surface of the ceramic plate.

[0011] An object of the present invention is to provide a ceramic firing carrier which, when used as a ceramic firing carrier, does not hinder the escape of gas during degreasing and has excellent airtightness for maintaining the environment of the ceramic during firing.

[0012] Means for solving problems

[0013] The inventors of the present application have studied the above-mentioned issues and found that, in the degreased body with reduced organic binder content, the concentration of impurities such as organic binder and sintering aid is deviated, which affects the properties of the ceramic plate obtained by firing. Such deviation is also affected by the carrier used during firing. More specifically, compared with the peripheral part of the green sheet, even if the organic binder is decomposed by heating, it is difficult for the inner part to escape to the outside of the sheet. In the sheet near the carrier, the carrier inhibits the escape of the decomposition gas of the organic binder. On the other hand, it was found that the carrier formed by using hexagonal boron nitride powder undergoes thermal expansion at high temperature, so although the effect of suppressing the escape of the sintering aid can be expected, the pore diameter does not shrink sufficiently (sometimes occluded) due to the relationship between the pore diameter and the thermal expansion coefficient, and the sintering aid escapes to the outside of the sheet before participating in the sintering of the ceramic raw material, and the sintering of the ceramic raw material becomes insufficient, and sometimes the expected strength cannot be exerted. The present invention is completed based on the relevant findings.

[0014] One aspect of the present invention provides a ceramic sintering carrier, which is composed of a boron nitride sintered plate having a plurality of pores, wherein the porosity is 8% by volume or more, and the proportion of pores with a pore diameter of 0.2 to 0.9 μm measured by a mercury porosimeter is 76 to 95% of all pores.

[0015] The above-mentioned ceramic firing carrier has a porosity greater than a specified value and a ratio of pores having a specified pore diameter in the pores within the above-mentioned range, thereby being able to maintain pores with a relatively large pore diameter in a temperature range in which the green sheet is degreased, and when used as a carrier, it is possible to easily remove the decomposition gas of organic matter contained in the green sheet. In addition, the above-mentioned ceramic firing carrier can reduce the pore diameter during high-temperature firing by shrinking at high temperatures, which is a characteristic of the boron nitride sintered plate. This effect can improve the airtightness of the degreased body (degreased green sheet) clamped in the carrier, thereby suppressing the escape of the sintering aid from the degreased body to the outside, and can be fired in a more uniform condition. With this effect, by using the above-mentioned ceramic firing carrier, sufficient sintering can be performed, and a high-quality ceramic plate with suppressed color unevenness can be manufactured.

[0016] The thermal expansion coefficient of the ceramic sintering carrier at 600° C. may be -1.0 ppm / K or more. The degreasing of the green sheet is performed at a relatively low temperature range of 600° C. or less. Therefore, by suppressing the thermal expansion coefficient at 600° C. to such a low shrinkage rate within the above range, it is possible to make it easier for the decomposition gas of the organic matter to escape.

[0017] In the ceramic firing carrier, the ratio of open pores to the pores may be 40% or more.

[0018] The iron content of the ceramic sintering carrier may be 30.0 ppm or less. By making the iron content within the above range, it is possible to further suppress adhesion with the ceramic raw material contained in the green sheet, and to manufacture a ceramic plate of higher quality. In addition, it is possible to further suppress color unevenness in the obtained ceramic plate.

[0019] The calcium content of the ceramic sintering carrier may be 100.0 ppm or less. By making the calcium content within the above range, it is possible to further suppress adhesion with the ceramic raw materials contained in the green sheet, and to manufacture a ceramic plate of higher quality. In addition, it is possible to further suppress color unevenness in the obtained ceramic plate.

[0020] The peak position of the pore diameter distribution curve of the ceramic firing carrier may be 0.25 μm or more. If the peak position of the pore diameter distribution curve is within the above range, the gas permeability during degreasing can be further improved, and a ceramic plate with less color unevenness can be manufactured.

[0021] The peak position of the pore diameter distribution curve of the ceramic sintering carrier may be 0.80 μm or less. If the peak position of the pore diameter distribution curve is within the above range, the bending strength of the carrier can be improved, the deformation of the carrier itself during sintering can be further suppressed, and a ceramic plate with better quality can be manufactured.

[0022] Effects of the Invention

[0023] According to the present invention, it is possible to provide a ceramic firing carrier which, when used as a ceramic firing carrier, does not hinder the escape of gas during degreasing and has excellent airtightness for maintaining the environment of the ceramic during firing. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] [ Figure 1 ] Figure 1 It is a perspective view showing an example of a carrier for ceramic firing. DETAILED DESCRIPTION

[0025] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings as appropriate. However, the following embodiments are examples for describing the present invention, and the present invention is not limited to the following contents. In addition, unless otherwise specified, the positional relationships such as up and down, left and right are based on the positional relationships shown in the accompanying drawings. In addition, the size ratios of the elements are not limited to the ratios shown in the drawings.

[0026] Unless otherwise specified, the material exemplified in this specification can be used alone or in combination of two or more. Unless otherwise specified, when each component in the composition corresponds to a plurality of substances, the content of each component in the composition represents the total amount of the plurality of substances present in the composition.

[0027] Figure 1 1 is a perspective view showing an example of a ceramic sintering carrier. The ceramic sintering carrier 100 is composed of a boron nitride sintered plate having a plurality of pores. The porosity of the ceramic sintering carrier 100 is 8% by volume or more, and the proportion of pores with a pore diameter of 0.2 to 0.9 μm measured by a mercury porosimeter is 76 to 95% of all pores. The size of the ceramic sintering carrier is not particularly limited, but if productivity is taken into consideration, a large area of ​​200 mm in length and 200 mm in width or more is preferably used in order to be able to sinter multiple pieces at the same time.

[0028] The porosity of the ceramic firing carrier 100 may be, for example, greater than 8% by volume, greater than 9% by volume, greater than 10% by volume, greater than 15% by volume, or greater than 20% by volume. From the perspective of suppressing the decrease in the mechanical strength of the carrier itself and more fully suppressing deformation when exposed to high temperatures, the upper limit of the porosity of the ceramic firing carrier 100 may be, for example, less than 45% by volume, less than 45% by volume, less than 43% by volume, less than 40% by volume, or less than 35% by volume. The porosity of the ceramic firing carrier 100 can be adjusted within the above range, for example, greater than 8% by volume and less than 43% by volume, or 9 to 43% by volume.

[0029] The porosity in this specification is a value measured by mercury intrusion porosimetry in accordance with JIS R 1655:2003 "Test method for pore distribution of molded bodies of fine ceramics by mercury intrusion porosimetry".

[0030] The proportion of pores with a pore diameter of 0.2 to 0.9 μm in all pores measured by a mercury porosimeter can be, for example, 77% or more, 78% or more, 79% or more, 80% or more, 85% or more, or 90% or more. The proportion of pores with a pore diameter of 0.2 to 0.9 μm in all pores measured by a mercury porosimeter is less than 95%, but can be, for example, less than 94% or less than 93%. The proportion of pores with a pore diameter of 0.2 to 0.9 μm in all pores measured by a mercury porosimeter can be adjusted within the above range, and can be, for example, 77 to 95%, or 80 to 95%.

[0031] The ratio of pores having the above-mentioned predetermined pore diameter can be calculated from a pore distribution curve measured by a mercury porosimeter.

[0032] By making the ratio of open pores (pores not closed to the outside space) in the pores of the ceramic firing carrier 100 high, for example, gas can be easily released during degreasing of the green sheet, and the effect of improving airtightness due to pore contraction caused by the expansion of boron nitride at high temperature can be more significantly obtained. The ratio of open pores in the above pores can be, for example, 40% or more, 50% or more, or 60% or more. The ratio of open pores in the above pores can also be 100%, but from the viewpoint of improving the bending strength, it can be 95% or less, or 90% or less.

[0033] The ratio of open pores to closed pores (the difference between all pores and open pores) in the pores of the ceramic firing carrier 100 can be determined by the following method using the Archimedes method. In the present invention, the porosity can be calculated based on the theoretical density calculated from the total porosity obtained by the Archimedes method and the volume density calculated from the size and mass of the boron nitride sintered body. The above-mentioned open porosity is measured in accordance with JIS R 1634:1998 "Determination method of density and open porosity of sintered bodies of fine ceramics". The closed porosity is calculated from the difference between the total porosity and the open porosity calculated by the above-mentioned method.

[0034] For the pores of the ceramic firing carrier 100, the peak position in the distribution curve of the pore diameter can be, for example, 0.25 μm or more, 0.28 μm or more, 0.30 μm or more, or 0.33 μm or more. If the peak position of the pore diameter is within the above range, the gas permeability during degreasing of the green sheet can be improved, so that a ceramic plate with less color unevenness can be manufactured.

[0035] For the pores of the above-mentioned ceramic sintering carrier 100, the peak position in the distribution curve of the pore diameter can be, for example, less than 0.80 μm, less than 0.70 μm, or less than 0.65 μm, less than 0.62 μm, less than 0.60 μm, or less than 0.57 μm. If the peak position of the pore diameter is within the above range, the bending strength of the carrier can be improved, the deformation of the carrier itself during sintering can be further suppressed, and a ceramic plate with better quality can be manufactured. The peak position in the distribution curve of the pore diameter can be adjusted within the above range, for example, it can be 0.25 to 0.80 μm.

[0036] The ceramic firing carrier 100 may contain metal elements from raw materials. Examples of the metal elements include iron, calcium, sodium, magnesium, silicon, chromium, nickel, and aluminum. When such metal elements are present on the main surface of the ceramic firing carrier 100, a green sheet or a ceramic plate in contact with the carrier may be welded to the carrier, so the content of the metal elements is preferably suppressed to a low level.

[0037] The iron content in the ceramics firing carrier 100 may be, for example, 30.0 ppm or less, 20.0 ppm or less, 10.0 ppm or less, 5.0 ppm or less, or 1.0 ppm or less.

[0038] The calcium content in the ceramic firing carrier 100 may be, for example, 100.0 ppm or less, 80.0 ppm or less, 60.0 ppm or less, 40.0 ppm or less, 20.0 ppm or less, or 10.0 ppm or less.

[0039] The content of metal elements such as iron and calcium refers to a value measured by a pressurized oxygen decomposition method using high-frequency inductively coupled plasma emission spectrometry (ICP emission spectrometry).

[0040] The thermal shrinkage of the ceramic firing carrier 100 at 600° C. is suppressed to be small. Therefore, even when used as a carrier in a green sheet degreasing process, the decomposition gas of the organic binder can easily escape to the outside through the carrier, and the content of the organic binder can be reduced, so that the ceramic can be fired in a state with further reduced impurities.

[0041] The thermal expansion coefficient of the ceramic firing carrier 100 at 600°C can be, for example, -1.00 ppm / K or more, -0.95 ppm / K or more, -0.90 ppm / K or more, -0.80 ppm / K or more, -0.70 ppm / K or more, or -0.60 ppm / K or more. Since the ceramic firing carrier 100 is made of boron nitride, the upper limit of the thermal expansion coefficient of the ceramic firing carrier 100 at 600°C is generally less than -0.30 ppm / K. The thermal expansion coefficient of the ceramic firing carrier 100 at 600°C can be adjusted within the above range, for example, from -1.00 to -0.30 ppm / K.

[0042] The thermal expansion coefficient in this specification means a linear expansion coefficient, and refers to a value measured by the method described in JIS R1618:2002 "Method for measuring thermal expansion of fine ceramics by thermomechanical analysis".

[0043] The ceramic sintering carrier 100 has excellent bending strength. Therefore, even if expansion occurs with temperature rise, deformation such as bending is suppressed. The bending strength of the ceramic sintering carrier 100 can be, for example, 15 MPa or more, 20 MPa or more, 25 MPa or more, or 30 MPa or more. The upper limit of the bending strength of the ceramic sintering carrier 100 can be, for example, 100 MPa or less, 80 MPa or less, 70 MPa or less, or 60 MPa or less.

[0044] The flexural strength in this specification refers to the three-point flexural strength measured in accordance with JIS R 1601:2008 "Test method for room temperature flexural strength of fine ceramics". The three-point flexural strength can be measured using a flexural strength tester.

[0045] The ceramic carrier for firing can be manufactured, for example, by the following method. An example of the manufacturing method of the ceramic carrier for firing includes: a first firing step of heating a mixture containing boron nitride powder at a heating temperature of 1800° C. or less for a predetermined time to obtain a heat-treated product; and a second firing step of heating a mixture at a heating temperature of 1900 to 2300° C. for a predetermined time to obtain a fired body from the heat-treated product.

[0046] Boron nitride powder can use a mixed powder of amorphous boron nitride powder and hexagonal boron nitride powder. From the viewpoint of improving the thermal conductivity of the carrier for ceramic sintering, it is desirable that the amount of hexagonal boron nitride powder in the mixed powder is large. Taking the total amount of boron nitride powder as 100 parts by mass, the amount of hexagonal boron nitride powder can be, for example, 15 to 85 parts by mass, or 20 to 80 parts by mass.

[0047] From the viewpoint of adjusting the pore diameter of the ceramic sintering carrier, it is preferred to use two or more boron nitride powders with different particle sizes. For example, a boron nitride with a small average particle size (boron nitride with a small particle size) and a boron nitride with a large average particle size (boron nitride with a large particle size) are used. From the viewpoint of improving thermal conductivity and transferring the temperature change around the ceramic sintering carrier to the green sheet and the degreased body, it is desirable to use hexagonal boron nitride powder as the boron nitride with a large particle size and amorphous boron nitride powder as the boron nitride with a small particle size.

[0048] The average particle size of the hexagonal boron nitride powder may be, for example, 10 μm or more, 20 μm or more, or 30 μm or more. The upper limit of the average particle size of the hexagonal boron nitride powder may be, for example, 100 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, or 50 μm or less.

[0049] The particle size distribution in the present invention can be measured according to the method described in JIS Z 8825:2013 "Particle size analysis-laser diffraction scattering method". In the cumulative distribution of the number-based particle size distribution thus measured, the particle size when the cumulative value from the small particle size reaches 50% of the total is the average particle size (D50). The measurement of the particle size distribution can be performed using, for example, Microtrac (manufactured by Nikkiso Co., Ltd., trade name: MT3300EXII).

[0050] From the viewpoint of suppressing the reduction of reaction sites with sintering aids and promoting liquid phase sintering, the lower limit of the total oxygen content of the boron nitride powder may be, for example, 0.3 mass %, 0.5 mass %, or 1.0 mass %. The upper limit of the total oxygen content of the boron nitride powder may be, for example, 3.0 mass %, 2.5 mass %, 2.0 mass %, 1.5 mass %, 1.2 mass %, 1.0 mass %, or 0.8 mass %.

[0051] The total oxygen content in this specification can be measured using an oxygen / nitrogen simultaneous analyzer. As the oxygen / nitrogen simultaneous analyzer, for example, an oxygen / nitrogen analyzer (trade name: EMGA-920) manufactured by Horiba, Ltd. can be used.

[0052] The mixture may further contain a sintering aid as required. Examples of the sintering aid include oxides of rare earth elements such as yttrium oxide, oxides such as aluminum oxide, magnesium oxide, and calcium oxide, carbonates of alkali metals such as lithium carbonate and sodium carbonate, and boron oxide.

[0053] For example, the amount of the sintering aid may be, for example, 0.01 parts by mass or more, or 0.10 parts by mass or more, relative to 100 parts by mass of the total of the boron nitride powder and the sintering aid. The amount of the sintering aid may be, for example, 5.00 parts by mass or less, 3.00 parts by mass or less, or 1.00 parts by mass or less, relative to 100 parts by mass of the total of the boron nitride powder and the sintering aid.

[0054] The mixture may further contain an organic binder, etc. as required. When the mixture contains an organic binder, the manufacturing method may include a degreasing step for decomposing and removing the organic binder before continuing the first calcination step and the second calcination step. The degreasing step may be performed, for example, at a heating temperature of 600° C. or less for 1 to 5 hours to decompose and remove the organic binder component from the mixture. Hereinafter, the mixture that has undergone the degreasing step is also referred to as a degreased body.

[0055] The preparation of the mixture can be carried out by dry grinding and dry mixing. However, in this case, the structure of the ceramic sintered body obtained by the aggregation of the raw material powder tends to become uneven. Therefore, it is preferred to use a ball mill or the like for wet grinding and wet mixing. In addition, a device with high dispersibility such as a bead mill can be used. The liquid solvent used in wet grinding and wet mixing can be an organic solvent, for example, it can be an alcohol. In order to further improve the formability, an organic binder is mixed with a ratio of less than 3% by mass relative to the solid content, and granulation can also be carried out by a spray dryer.

[0056] The obtained mixture may also be pre-pressed into a prescribed shape. From the viewpoint of obtaining a ceramic sintered body with reduced anisotropy, the forming may be performed using, for example, a cold isostatic pressing device (CIP). In the case where the bulk density of the mixture is high and the formability is low, mold forming may also be performed before CIP. The formed shape is not particularly limited, and may, for example, be a prism shape or a cylindrical shape.

[0057] The porosity of the obtained ceramic sintering carrier can be adjusted by the pressure during molding. The pressure during molding may be, for example, 5 to 500 MPa, 20 to 500 MPa, 80 to 500 MPa, 80 to 120 MPa, 120 to 300 MPa, or 300 to 500 MPa.

[0058] The firing may be performed using a heating and pressing molding machine such as a hot press, and a batch furnace or a continuous furnace may be used. Examples of the batch furnace include a muffle furnace, a tubular furnace, and an atmosphere furnace. Examples of the continuous furnace include a tunnel furnace, a belt furnace, a pusher furnace, and a piano-shaped continuous furnace.

[0059] The calcination can be performed in an atmosphere containing at least one selected from the group consisting of a rare gas and an inert gas. The rare gas may contain, for example, argon and helium, or may contain or consist of argon. The inert gas may be, for example, nitrogen.

[0060] The calcination can be performed under normal pressure or under pressure. The pressure during calcination can be, for example, 0.1 MPa or more, 1.0 MPa, 5.0 MPa, 10.0 MPa or more, 15.0 MPa or more, or 20.0 MPa or more.

[0061] The first calcining step is a step of obtaining a heat-treated product from the mixture or the degreased body by heating at an intermediate temperature of 1800° C. or lower for a predetermined time.

[0062] The heating temperature in the first calcining step may be, for example, 1200° C. or higher, or 1300° C. or higher. The heating temperature in the first calcining step may be, for example, 1750° C. or lower.

[0063] The calcination time in the first calcination step may be, for example, 1 to 10 hours, 2 to 10 hours, or 2 to 8 hours.

[0064] The firing time in this specification refers to the time (holding time) during which the temperature of the atmosphere in which the above-mentioned mixture or other object to be fired is placed is maintained after reaching the above-mentioned firing temperature.

[0065] The second calcination step is a step of obtaining a calcined body from the heat-treated product by performing a heat treatment at a high temperature of 1900 to 2300° C. for a predetermined time.

[0066] The heating temperature in the second calcining step may be, for example, 1950° C. or higher, or 2000° C. or higher. The heating temperature in the second calcining step may be, for example, 2200° C. or lower, or 2100° C. or lower.

[0067] The firing time in the second firing step may be, for example, 1 to 15 hours, 3 to 15 hours, or 3 to 10 hours.

[0068] Although several embodiments have been described above, the present invention is not limited to the above embodiments. In addition, the descriptions of the above embodiments can be applied to each other.

[0069] Example

[0070] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples. It should be noted that the present invention is not limited to the following Examples.

[0071] (Example 1)

[0072] 79 mass % of amorphous boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 1.5 mass %, boron nitride purity 97.0%) and 20 mass % of hexagonal boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 0.3 mass %, boron nitride purity: 99.0%, average particle size: 15 μm) were weighed in a container, and 1 mass % of a sintering aid (boron oxide) was added, and then crushed and mixed with a ball mill to prepare a mixed powder of nitrides. It should be noted that the total oxygen content of the boron nitride powder (mixed powder of amorphous boron nitride powder and hexagonal boron nitride powder) was 1.2 mass %.

[0073] The mixed powder was filled in a hot press device, preformed by pressurizing the mixed powder at 5 MPa, and then heated while applying a pressure of 20 MPa to sinter it, thereby preparing the ceramic sintering carrier of Example 1. It should be noted that in the heating treatment of the hot press, first, it was kept at 1450°C for 3 hours (first sintering), and then kept at 2000°C for 5 hours (second sintering) to sinter the mixed powder.

[0074] A plate having a thickness of 5 mm was cut out from the obtained nitride sintered body, and this was used as a ceramic firing carrier in Example 1.

[0075] (Example 2)

[0076] 40% by mass of amorphous boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 1.5% by mass, boron nitride purity 97.0%) and 60% by mass of hexagonal boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 0.3% by mass, boron nitride purity: 99.0%, average particle size: 15 μm) were weighed in a container, and an organic binder and water were added and mixed, followed by drying and granulation to obtain a mixed powder of nitrides. The obtained mixed powder was filled in a cold isostatic pressing (CIP) device (manufactured by Kobe Steel, Ltd., trade name: ADW800), and a pressure of 500 MPa was applied to the mixed powder to compress it to obtain a molded body. In order to decompose and remove the organic binder, the obtained molded body was heated at a heating temperature of 600°C for 5 hours, and the organic binder component was decomposed and removed from the mixture to obtain a degreased body. Then, a batch-type high-frequency furnace (manufactured by Fuji Electric Industry Co., Ltd.) was used to maintain it at 1400°C for 2 hours (first sintering), and then, it was maintained at 2050°C for 10 hours (second sintering) to sinter it, thereby preparing a nitride sintered body. It should be noted that for sintering, nitrogen was introduced into the furnace under a standard state so that the flow rate became 10L / min, while the furnace was adjusted under a nitrogen atmosphere, and the pressure was 0.1MPa (normal pressure). It should be noted that the total oxygen content of the boron nitride powder (mixed powder of amorphous boron nitride powder and hexagonal boron nitride powder) was 0.8% by mass.

[0077] A plate having a thickness of 5 mm was cut out from the obtained nitride sintered body, and this was used as a ceramic firing carrier in Example 2.

[0078] (Example 3)

[0079] A ceramic sintering carrier was prepared in the same manner as in Example 2 except that the cold isostatic pressing (CIP) pressure in the forming step was changed to 100 MPa.

[0080] (Example 4)

[0081] A ceramic carrier for firing was prepared in the same manner as in Example 2 except that the amorphous boron nitride powder used in the preparation of the mixed powder was changed to an amorphous boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 2.0 mass %, boron nitride purity: 96.2%). It should be noted that the total oxygen content of the boron nitride powder (mixed powder of amorphous boron nitride powder and hexagonal boron nitride powder) was 1.0 mass %.

[0082] (Example 5)

[0083] A ceramic firing carrier was prepared in the same manner as in Example 2 except that the heating temperature in the second firing was changed to 2000°C.

[0084] (Example 6)

[0085] A ceramic firing carrier was prepared in the same manner as in Example 2 except that the heating temperature in the first firing was changed to 1800°C and the heating temperature in the second firing was changed to 2000°C.

[0086] (Comparative Example 1)

[0087] Only amorphous boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 1.8 mass%, boron nitride purity 96.6%) was used (hexagonal boron nitride powder was not used), 1 mass% boron oxide and 0.5 mass% calcium oxide were added as sintering aids, the crushed and mixed powder was used as a mixed powder, the heating temperature in the first sintering was changed to 1400°C, the holding time was changed to 2 hours, and the heating temperature in the second sintering was changed to 1650°C, the holding time was changed to 5 hours. Except for this, a ceramic sintering carrier was prepared in the same manner as in Example 1.

[0088] (Comparative Example 2)

[0089] A ceramic carrier for firing was prepared in the same manner as in Example 1 except that 70% by mass of amorphous boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 2.8% by mass, boron nitride purity: 95.0%) and 30% by mass of hexagonal boron nitride powder (manufactured by Denka Co., Ltd., total oxygen content: 0.3% by mass, boron nitride purity: 99.0%, average particle size: 15 μm) were mixed, 1% by mass of boron oxide and 0.5% by mass of calcium oxide were added as sintering aids, the crushed and mixed powders were used as mixed powders, the heating temperature in the first firing was changed to 1400° C., the holding time was changed to 2 hours, and the heating temperature in the second firing was changed to 1550° C., the holding time was changed to 5 hours. It should be noted that the total oxygen content of the boron nitride powder (mixed powder of amorphous boron nitride powder and hexagonal boron nitride powder) was 2.1% by mass.

[0090] (Comparative Example 3)

[0091] A ceramic firing carrier was prepared in the same manner as in Example 2 except that the pressure of CIP molding was changed to 30 MPa, the first firing was not performed, and the heating temperature of the second firing was changed to 2000°C.

[0092] (Comparative Example 4)

[0093] A ceramic firing carrier was prepared in the same manner as in Example 2 except that the pressure of CIP molding was changed to 50 MPa, the first firing was not performed, and the heating temperature of the second firing was changed to 2000°C.

[0094] <Measurement of physical properties of ceramic sintering carriers>

[0095] The ceramic firing carriers prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were measured for porosity, the ratio of pores having a pore diameter of 0.2 to 0.9 μm measured by a mercury porosimeter, the iron content, the calcium content, and the thermal expansion coefficient at 600° C. The results are shown in Table 1.

[0096] <Evaluation of ceramic firing carriers>

[0097] The ceramic firing carriers prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were used to perform ceramic firing, and the performance as carriers was evaluated from the perspective of the strength and color unevenness of the obtained ceramic plates. It should be noted that during the evaluation, a ceramic firing carrier processed to 100 mm in length, 100 mm in width, and 5 mm in thickness was used.

[0098] Specifically, 94 parts by mass of silicon nitride powder, and 3 parts by mass of magnesium oxide and 3 parts by mass of yttrium oxide as sintering aids are weighed in a container, and a mixture is obtained by mixing. 25 parts by mass of an organic binder is added to the mixture, and after adding 150 parts by mass of ethanol, silicon nitride balls are used for mixing to obtain a slurry. After adjusting the viscosity of the obtained slurry, it is formed by a scraper method, and a green sheet with a length of 100 mm, a width of 100 mm, and a thickness of 0.4 mm is prepared using a pressing device. After boron nitride slurry is applied to one side of the green sheet and dried, 10 sheets are stacked and clamped with the above-mentioned ceramic sintering carrier to prepare a laminate. The laminate is left to stand in a heating furnace, degreased at 600°C for 5 hours, and then sintered at a sintering temperature of 1800°C for 5 hours to obtain a ceramic plate formed of silicon nitride.

[0099] [Measurement and evaluation of the strength (bending strength) of ceramic plates]

[0100] The strength of the ceramic plate prepared as described above was measured and evaluated according to the following criteria. The strength of the ceramic plate was measured using a commercially available universal testing machine in accordance with JIS R 1601:2008 "Test method for room temperature flexural strength of fine ceramics". The measured flexural strength values ​​were evaluated according to the following criteria.

[0101] A: Bending strength is greater than 30MPa.

[0102] B: Bending strength is 15 to 30 MPa.

[0103] C: Flexural strength is less than 15 MPa.

[0104] [Evaluation of color unevenness of ceramic plates]

[0105] In order to quantitatively evaluate the color unevenness of the ceramic plate prepared as described above, the oxygen content was measured as follows and evaluated according to the following criteria. Samples with a size of 5 mm in length and 5 mm in width were collected diagonally from one corner of the ceramic plate formed of silicon nitride toward the center, and each sample was crushed into powder, and the oxygen content was measured using an oxygen / nitrogen analyzer in the same manner as the carrier for ceramic sintering.

[0106] A: The difference between the maximum value and the minimum value of the measured oxygen amount is 0.10 or less.

[0107] B: The difference between the maximum value and the minimum value of the measured oxygen amount is greater than 0.10 and less than 0.20.

[0108] C: The difference between the maximum and minimum values ​​of the measured oxygen content is greater than 0.20.

[0109] [Table 1]

[0110]

[0111] Industrial Applicability

[0112] According to the present invention, it is possible to provide a ceramic firing carrier which, when used as a ceramic firing carrier, does not hinder the escape of gas during degreasing and has excellent airtightness for maintaining the environment of the ceramic during firing.

[0113] Description of Reference Numerals

[0114] 100…Ceramic firing carrier.

Claims

1. A ceramic sintering carrier, which is composed of a boron nitride sintered plate having a plurality of pores, The porosity of the ceramic sintering carrier is 8 volume % or more, The proportion of pores having a pore diameter of 0.2 to 0.9 μm measured by a mercury porosimeter is 76 to 95% of all pores.

2. The ceramic sintering carrier according to claim 1, wherein the thermal expansion coefficient at 600°C is -1.00 ppm / K or more.

3. The ceramic sintering carrier according to claim 1 or 2, wherein: The proportion of open pores in the pores is more than 40%.

4. The ceramic sintering carrier according to claim 1 or 2, wherein: The iron content is 30.0 ppm or less.

5. The ceramic sintering carrier according to claim 1 or 2, wherein: The calcium content is 100.0 ppm or less.

6. The ceramic sintering carrier according to claim 1 or 2, wherein: The peak position in the distribution curve of pore diameters is 0.25 μm or more.

7. The ceramic sintering carrier according to claim 1 or 2, wherein: The peak position in the distribution curve of pore diameters is 0.80 μm or less.

Citation Information

Patent Citations

  • Setter for ceramic firing

    JP1997278526A

  • Degreasing / Burning implement for aluminum nitride molded form

    JP2000119068A

  • Porous ceramic thin plate and method of manufacturing ceramic sheet using thin plate

    JP2007001860A